Il fotografo al lavoro: gli album di Cesare Giulio (1890-1946) - Varoli, Valentina (Rivista di studi di fotografia. Journal of Studies in Photography, 2018)
Close analysis of the 147 photographic albums of Italian photographer Cesare Giulio (1890-1946) allows us to understand the author’s way of working and his evolving ideas about the medium. Three different types of objects are preserved in the photographer’s archive: proof sheet, dating mainly from the 1910s; albums meant as visual memories of his excursions in the Alps during the first half of the 1920s; and a set of “accurate tests” related to the artist’s evolution toward a more modernist approach in the second half of that decade. As a whole, these albums shed new light on the work of a less-known Italian photographer who nevertheless had a deep influence on Italian modern photography in the interwar period.